tính nhanh
9812 x 143 - 42 x 9812 - 9812
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
= 9812 x 143 - 42 x 9812 - 9812 x 1
= 9812 x ( 143 - 42 - 1 )
= 9812 x 100
= 981200
~ Hok Tốt ~
=145x(99+1)-143x(101-1)
=145x100 - 143x100
=100x(145-143)
=100x2
=200
(145 x 99 + 145 ) - ( 143 x 102 – 143 × 2 ) + 54 x 47 - 47 x 53 - 20 - 27
= 145 × (99 + 1) – 143 × (102 – 2) + 47 × (54 – 53) – (20 + 27)
= 145 × 100 – 143 × 100 + 47 × 1 – 47
= 100 × (145 – 143) + (47 – 47)
= 100 × 2 + 0
= 200
= 145 x (99+1) - 143 x ( 102-2) + 47 x ( 54 - 53) -20-27
= 145 x 100 - 143 x 100 + 47 x 1 -20-27
= 100 x ( 145 - 143 ) + 47 - 20 - 27
= 200 + 47 - 20 - 27
= 200
(145 x 99 + 145 ) - ( 143 x 102 – 143 × 2 ) + 54 x 47 - 47 x 53 - 20 - 27
= 145 × (99 + 1) – 143 × (102 – 2) + 47 × (54 – 53) – (20 + 27)
= 145 × 100 – 143 × 100 + 47 × 1 – 47
= 100 × (145 – 143) + (47 – 47)
= 100 × 2 + 0
= 200
(145 x 99 + 145 ) - ( 143 x 102 – 143 × 2 ) + 54 x 47 - 47 x 53 - 20 - 27
= 145 × (99 + 1) – 143 × (102 – 2) + 47 × (54 – 53) – (20 + 27)
= 145 × 100 – 143 × 100 + 47 × 1 – 47
= 100 × (145 – 143) + (47 – 47)
= 100 × 2 + 0
= 200
(145 x 99 + 145) - (143 x 102 - 143)
=(145 x (99+1) - (143 x (102-1)
=(145 x 100) - (143 x 101)
=14500 - 14443
=57
Chúc bạn học tốt .
Ta có: ( 145 x 99 + 145 ) - ( 143 x 102 - 143 )
= [145.(99 + 1)] - [143.(102 - 1)]
= (145.100) - (143.101)
= .........................
Đề:.............
= 145 x (99 + 1) - 143 x (101 - 1)
= 145 x 100 - 143 x 100
= 14500 - 14300
= 2
(145x99+145)-(143x101-143)
=145x(99+1)-143(101-1)
=145x100-143x100
=14500-14300=200
a, 4 x 113 x 8 - 32 x 13
= (4 x 8) x 113 - 32 x 13
= 32 x 113 - 32 x 13
= 32 x (113 - 13)
= 32 x 100 = 3200
b , 54 x 227 + 45 x 227 + 227
= 227 x (54+45+1)
= 227 x 100
= 22 700
c, ( 145 x 99 + 145 ) - ( 143 x101 - 143 )
= 145 x (99+1) - 143 x (101 - 1)
= 145 x 100 - 143 x 100
= 100 x (145 - 143)
= 100 x 2
= 200
a) \(4\times113\times8-32\times13\)
\(=4\times8\times113-32\times13\)
\(=32\times113-32\times13\)
\(=32\times\left(113-13\right)\)
\(=32\times100\)
\(=3200\)
b) \(54\times227+45\times227+227\)
\(=227\times\left(54+45+1\right)\)
\(=227\times100\)
\(=22700\)
c) \(\left(145\times99+145\right)-\left(143\times101-143\right)\)
\(=145\times\left(99+1\right)-143\left(101-1\right)\)
\(=145\times100-143\times100\)
\(=14500-14300\)
\(=200\)
= 9812 x 143 - 42 x 9812 - 9812 x 1
= 9812 x ( 143 - 42 - 1 )
= 9812 x 100
= 981200
########
`HT`
9812 x 143 - 42 x 9812 - 9812
= 9812 x (143 - 42 - 1)
= 9812 x 100
= 981200